The effect of herbicide glufosinate ammonium 150 g/L dose on several weeds and potatoes (Solanum tuberosum L.) yield - Kurniadie, Denny; Sumekar, Yayan; Valent, Chika (Universitas Padjadjaran, 2023)
In the last three years, potato production in Indonesia fluctuated every year. One of the factors that cause low productivity of potatoes is weed. The presence of weeds in potato planting areas can inhibit plant growth and affect potato yields. The aim of this study is to determine the effectiveness of herbicide glufosinate ammonium 150 g/L to control common weeds in potato plants. This research was conducted in a farmer field in Lebak Muncang Village, Ciwidey District, Bandung Regency, West Java Province. The experimental design used was a randomized block design with six treatments and four replications. Weed control using the herbicide glufosinate ammonium 150 g/L at a dose of 2.75– 4.50 L/ha was completely (100%) controlled Eleusine indica, Galinsoga parviflora, Amaranthus spinosus, Richardia brasiliensis, and total weeds for up to 6 weeks after application without causing symptoms of poisoning and could increase the number of potato tuber per plant and yield of potato per plot.